2017
DOI: 10.29252/ijn.30.105.11
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Mindfulness and Meta-Emotion on Predicting Emotional Adjustment of Novice Nurses

Abstract: Background & Aim: New graduate nurses suffer high levels of stress which can lead to unpleasant personal and professional outcomes. The aim of this study was to investigate the role of mindfulness and meta-emotion on predicting Emotional Adjustment in novice nurses. Material & Method: The descriptive-correlative method was used for conducting this research. The Statistical population was consisted of all the nurses in Tabriz. A sample of 120 subjects (60 females and 60 males) was randomly selected, using multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Additionally, this scale had a positive correlation (convergent validity) and a negative correlation (differential validity) with other scales, such as NEO-FFI, NEO-PI, Beck depression scale, Rosenberg self-esteem scale, and Spielberger State-Trait anxiety inventory (9). In a study (10), the validity of the was confirmed by professors and its reliability was 0.87 using the Cronbach's alpha coefficient. In the current study, using Cronbach's alpha coefficient, the overall reliability of this scale was 0.74.…”
Section: Mindful Attention Awareness Scalementioning
confidence: 79%
“…Additionally, this scale had a positive correlation (convergent validity) and a negative correlation (differential validity) with other scales, such as NEO-FFI, NEO-PI, Beck depression scale, Rosenberg self-esteem scale, and Spielberger State-Trait anxiety inventory (9). In a study (10), the validity of the was confirmed by professors and its reliability was 0.87 using the Cronbach's alpha coefficient. In the current study, using Cronbach's alpha coefficient, the overall reliability of this scale was 0.74.…”
Section: Mindful Attention Awareness Scalementioning
confidence: 79%
“…The findings of Heidari et al [12] showed the importance of mindfulness, emotional intelligence, and general self-efficacy in predicting and reducing perceived stress. Results of Babaei et al [13] showed a positive and significant correlation between mindfulness and positive emotional-cognitive regulation. Duan [14] research on mindfulness and its role in reducing stress and mental health, suggests that training mindfulness can recognize the strengths and weaknesses of the care providers.…”
mentioning
confidence: 90%
“…Babaei Nadinluye et al (14) figured out that there was a direct and significant correlation between mindfulness and positive cognitive emotion regulation and a diverse relationship between negative cognitive emotion regulation and mindfulness. Norouzi and Hashemi (15) demonstrated that mindfulness-based cognitive therapy was beneficial for improving emotion regulation and psychosocial and self-care outcomes of patients with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%